DEATH NOTE: CONJURAÇÕES ENTRE AUTORIA, ESCRITA E MORTE - Theodorovicz, Viviane (2014)
This dissertation presents the results of a study concerning the relationship between the process of writing and authorship in the 37-episode Japanese animê, Death Note, adapted by Tetsuro Araki, from the manga series which has the same name, written by Tsugumi Oba and illustrated by Takeshi Obata, in which a young student finds a notebook with supernatural powers. Then, he ends up using the notebook in a tyrannical manner, watching and punishing the humankind. Among these episodes, the first 13 ones were listed for analysis. In the first topics of the dissertation it is approached the way the impasses of writing are configured, the construction of Kira as the Old Testament God, the disguise of the voice and the name and the circumstances of the trial and punishment of Kira. Subsequently, the issues concerning death and authorship are exposed. Finally, it is discussed some issues related to the desire of communicating and the influence on the performance to ensure the difference. This study will mainly be done through the analysis of the characters Raito and Ryuuku, considering that the first will work as a metaphor for the concept of authorship and the other as influence. Raito is read, in this study, as the carrier of the writing disease, someone who does not see himself in his own work, and therefore, he always returns to it in an infinite work. In the attempt of ensuring his work and his role as the new world`s God, Raito is renamed as Kira, whose identity strength has suppressed the previous one. The character Ryuuku appears as a ghost of the influence, whose role is just to hover over the work without acting on it. It is also intended to take into consideration, during the anime analysis, the title, that since the beginning, prophesies a relationship with death that dialogues with post structuralist theories of authorship and writing.